A Correlational Study of Motivation and Language Anxiety For Learning Chinese as A Foreign Language with Chinese Academic Achievement of Thai Grade 6 Students - Zheng, Ying; Richard Lynch (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Abstract: The purpose of this quantitative correlational study was to determine whether there was a significant relationship between. A target student for the study are 164 Grade 6 students from Thai government school in Trang, Thailand. Motivation and Language Anxiety for Learning Chinese as a Foreign Language Questionnaire was used to collect data from a total of 164 students. The survey questionnaire was adapted from the five subscales known as Motivational Intensity, Desire to learn Chinese as a foreign language (CFL), Attitude toward learning CFL, Language use anxiety and language class anxiety from international version of Gardner’s (2004) Attitude/Motivation Test Battery The researcher finds the relationship among the motivation and language anxiety for learning Chinese as a foreign language with their Chinese academic achievement using multiple correlation coefficient. Descriptive statistics (means, standard deviation), correlational analysis was used to analyze the data. The research finding indicated that Grade 6 students displayed a slightly low level of motivation and a slightly low level of language anxiety for learning Chinese as a foreign language. The research found that there was very weak relationship between Grade 6 students’ motivation and their language anxiety for learning Chinese as a foreign language with Chinese academic achievement at a Thai government school in Trang.